A review and perspective on industry high-temperature heat pumps. (June 2022) - Jiang, Jiatong; Hu, Bin; Wang, R.Z.; Deng, Na; Cao, Feng; Wang, Chi-Chuan
Abstract: A reduction of CO2 emission from heating industry is urgently required due to the transition of industry towards carbon neutrality. The High-temperature Heat Pump (HTHP) is a valid alternative technology for heating while enhancing energy utilization efficiency to potentially contribute to carbon neutral electrification. Therefore, this study proposes some future development directions for HTHPs based on the current state of research and application cases to accelerate the replacement of industrial boilers. The laboratory-scale HTHPs with heat sink temperature higher than 80 °C are reviewed following different configurations, including single-stage, multi-stage, cascade, hybrid system, etc. Among these experimental researches, about 71% of the prototypes were charged with low Global Warming Potential (GWP) refrigerants. Besides, HTHPs with large temperature lift is a must in practice, and some even achieved temperature lift above 100 °C. For the application researches, the heating capacity of reviewed HTHPs applied in industry ranged from 60 kW to 18 MW with output temperature higher than 80 °C. High-GWP refrigerants, especially R245fa and R134a, are the mainstream refrigerants for applications until now, accounting for 67% of the reviewed cases. The remaining units were charged with natural refrigerants, and no reports are available for new synthetic refrigerant (e.g. HFOs, HCFOs). Based on the comprehensive review of HTHPs from laboratory and application, four suggestive prospects are revealed for HTHPs, being i) low-GWP refrigerants; ii) output temperature higher than 100 °C; iii) heating capacity larger than 1 MW; iv) Coefficient of Potential (COP) larger than 4 under 40 °C temperature lift. Highlights: State of art of HTHPs is concluded from configurations, refrigerants and applications. Challenges of HTHPs development from refrigerants, configuration, components are summarized. Perspectives for industrial HTHPs are proposed to promote industrial boilers replacement. HTHPs with COP of 4.0 can achieve the its carbon neutrality under ecological decarburization. The four prospects of HTHP are proposed for Ultra Heat Pump.